Efficacy of selected grain protectants on hulled Kernza®, dehulled Kernza®, and hard red winter wheat against two economically important stored product insect species - Bhattarai, Natasha (My University, 2024)
No grain protectants are currently registered for use on the perennial grass, Thinopyrum intermedium (Host) Barkworth & D.R. Dewey (Poales: Poaceae), marketed under the trade name Kernza®. Phosphine is the only fumigant approved for treating perennial grasses. The efficacy of selected commercial formulations of grain protectants namely, deltamethrin, methoprene, methoprene plus deltamethrin, and spinosad on hulled and dehulled Kernza® were evaluated at labeled rates in the laboratory against the lesser grain borer, Rhyzopertha dominica (Fabricius) (Coleoptera: Bostrichidae) and rice weevil, Sitophilus oryzae (Linnaeus) (Coleoptera: Cucrculionidae). The concentrations of the protectants used were 0.5 and 1 ppm for deltamethrin, 1.25 ppm methoprene, 1.25 ppm methoprene plus 0.5 ppm deltamethrin as a combination product, and spinosad at 1 ppm. At each concentration of an insecticide, 100 g of dehulled Kernza®, hulled Kernza®, and hard red winter wheat were treated and placed in 0.47-L glass mason jars. Into each jar, 50 unsexed adults of mixed ages of R. dominica or S. oryzae were added, after which the jars were closed with metal lids fitted with wire mesh screens and filter papers. Jars with insects were placed in environmental growth chambers at 28ºC and 65% r.h. Mortality was assessed on independent samples after 7, 14, and, 21 days post-infestation. Mortality of the insects was expressed as percentage of the total insects exposed. In separate replicates, all three grain types were treated with the same protectants and infested as described above. These jars were checked after 42 days to count adult progeny produced. After determination of adult progeny production, the grains were passed through the Boerner divider® to get a working sample of 6 g for wheat and 1.5 g for hulled and dehulled Kernza®. From the working sample, the number of damaged and undamaged kernels were counted, and their weights were measured to determine grain weight loss and expressed as a percentage. The results showed that high mortality (> 90%) of R. dominica adults, low progeny production, and low grain weight loss were observed at 7, 14, and 21 days in dehulled Kernza® and hard red winter wheat at 0.5 and 1 ppm of deltamethrin. The mortality of S. oryzae adults was > 50% after 14 and 21 days of exposure to the two deltamethrin concentrations on all grain types. No or very low adult progeny numbers were observed in all grain types treated with both concentrations of deltamethrin. Low mortality (< 50%) of both insect species were observed in methoprene treated grains at all observation times. However, low adult progeny numbers were obtained in methoprene treated grains despite low mortality of adults. In methoprene plus deltamethrin treatments, the mortality of R. dominica adults was ≥ 93% in all grain times at all observation times, whereas the mortality of S. oryzae on all grain types and observation times ranged from 60 to 100%. There was no progeny production of R. dominica on all grain types, whereas S. oryzae mean progeny production at 7, 14, and 21 days ranged from 0 to 2.4 adults/jar; at 42 days adult progeny production ranged from 0.8 to 21.2 adults/jar. Grain weight loss was < 0.2 to 0.9% in treated grains exposed to R. dominica and S. oryzae. Spinosad caused 100% mortality of R. dominica adults and no progeny were produced, and no grain weight loss was observed on all grain types and observation times. In the case of S. oryzae, mean adult mortality at 7, 14, and 21 days in treated grains ranged from 87.2 to 100%, and progeny production and grain weight loss ranged 0 to 21.4 adults/jar and 0%, respectively. Spinosad at 1 ppm, deltamethrin at 0.5 and 1 ppm, methoprene and deltamethrin at 1.25 + 0.5 ppm were most effective grain protectants on Kernza® against R. dominica. In conclusion, spinosad at 1 ppm was the most effective grain protectant on Kernza® against R. dominica and S. oryzae. For dehulled Kernza the efficacy of tested grain protectants could not be satisfactorily gauged because of high mortality of R. dominica and S. oryzae adults in the control treatments.
Keywords: Kernza®; Stored-product insects; Efficacy assessment; Grain protectants